Academic leadership day by day small steps that lead to great success - Buller, Jeffrey L. (Jossey-Bass, 2010)
"It can seem at times as though all of academic administration today is focused only on the need for continual change and the endless pursuit of "the big idea." But most academic leaders, from department chairs and program directors through university presidents and chancellors, are far too busy helping their institutions flourish for them to divert critical energy and resources to yet another untried theory or management principle. Academic Leadership Day by Day takes an entirely different approach to developing your proven academic leadership: It introduces one practical and field-tested idea each day for an entire academic year. Rather than requiring you to devote days or even weeks to administrative training (which may prove to be of little use in he end), this manual gives you non-nonsense suggestions that you can consider on even your busiest days. Experiment with the suggestions made each day, discover what works for you, and then build on your successes for the benefit of your institution and its programs. Significant improvements often result from small, gradual, and consistent efforts, and Academic Leadership Day by Day is your guide to becoming a more accomplished, confident academic leader a few minutes at a time."--